Pengaruh Kecepatan Putaran Menggunakan Pahat Karbida Tungsten Kobalt 6% terhadap Frekuensi Getaran dan Kekasaran Permukaan Baja ST 37 - Chendri Johan; Paulus Aket; Rony Rukka; Lery Alfriany Salo (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2026)
This study aims to analyze the effect of rotational speed variations in the turning process using 6% cobalt tungsten carbide chisels on the vibration frequency and surface roughness of ST 37 steel. Tests were conducted using a conventional lathe with five rotational speed variations: 350 rpm, 400 rpm, 450 rpm, 500 rpm, and 550 rpm. Other cutting parameters were kept constant, namely feed rate of 0.7 mm/rev, depth of cut of 0.7 mm, and the use of SAE 10 oil cooling media. The results showed that the higher the rotational speed, the lower the surface roughness value. The highest roughness value was obtained at a speed of 350 rpm of 7.420 μm, while the lowest value was at 550 rpm of 4.66 μm. Conversely, the vibration frequency increased with increasing rotational speed. The lowest vibration frequency of 1.53 mm/s occurred at 350 rpm, while the highest value was 3.53 mm/s at 550 rpm. These results show that increasing the rotational speed produces a smoother surface, but increases tool vibration.